Evaluation of Contrast Flow Patterns with Cervical Interlaminar Epidural Injection: Comparison of Midline and Paramedian Approaches - Lee, Byeongcheol (Medicina (Kaunas), 2020)
Background and objectives: The purpose of this study was to compare and to analyze contrast spread patterns between the paramedian and midline approaches to cervical interlaminar epidural injection (CIEI). Materials and Methods: We retrospectively enrolled 84 CIEI cases that had been performed for unilateral cervical spinal pain from April 2019 to April 2020. After 3 mL of contrast had been injected into the epidural space, fluoroscopic images were obtained. The CIEI was divided into a midline (Group M, n = 42) and a paramedian (Group P, n = 42) approach by anteroposterior imaging. The P Group was classified into a more medial (Group Pm, n = 26) and a more lateral (Group Pl, n = 16) group. Using ImageJ on an anteroposterior image, we assessed the grayscale brightness ratio of the ipsilateral or contralateral side of the vertebral body as well as the intervertebral disc space one level just above the needle location. We identified the dispersion of contrast into the ventral epidural space. Results: The grayscale brightness ratio was significantly higher in Group P than in Group M (p < 0.001). The incidence of ventral epidural spread in Group M was 57.1% versus 88.1% in Group P, which was significantly different (p = 0.001). Conclusions: The fluoroscopic CIEI finding in the paramedian approach predominantly showed an excellent delivery of the injectate to the ipsilateral side in comparison to the contralateral side. This showed a greater advantage in delivery toward ventral epidural space as compared to the midline approach.